Development of Desktop-Based Employee Payroll: A Case Study on PT. Bio Pilar Utama - Alfia, Bayu Dwiki; Asroni, Asroni; Riyadi, Slamet; Rahaman, Mosiur (Universitas Muhammadiyah Yogyakarta, 2023)
As a result of periodic shifts, technological advancements are becoming more varied. The payroll system for employees is one of them. Payroll must follow the company’s standard operating procedures (SOP) to determine several issues. Thus, the system can be customized to match the company’s specific needs and SOP. The administration and finance departments encounter difficulty processing employee payroll due to frequent errors in employee data entry, including position, department, income, and deductions. The absence of a payroll information system that can reliably and rapidly calculate employee salaries and provide timely reports has become the primary source of the difficulty. The designed employee payroll information system only processed PT. Bio Pilar Utama’s payroll data. Facilitating the administration and finance departments to input data, calculate salaries, store data, and generate reports on employee payroll could be achieved through the newly developed employee payroll information system.